2020
DOI: 10.1186/s13550-020-0607-5
|View full text |Cite
|
Sign up to set email alerts
|

Spinal cord hypermetabolism extends to skeletal muscle in amyotrophic lateral sclerosis: a computational approach to [18F]-fluorodeoxyglucose PET/CT images

Abstract: Purpose Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disease leading to neuromuscular palsy and death. We propose a computational approach to [18F]-fluorodeoxyglucose (FDG) PET/CT images to analyze the structure and metabolic pattern of skeletal muscle in ALS and its relationship with disease aggressiveness. Materials and methods A computational 3D method was used to extract whole psoas muscle’s volumes and average attenuation coeffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

5
3

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 36 publications
3
14
0
Order By: Relevance
“…The present study confirms that the increased skeletal muscle FDG uptake observed in ALS patients also occurs in the SOD1 G93A experimental model [9]. The increase in FDG accumulation rate was observed in living mice, under fasting conditions and in the presence of normal glucose levels.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The present study confirms that the increased skeletal muscle FDG uptake observed in ALS patients also occurs in the SOD1 G93A experimental model [9]. The increase in FDG accumulation rate was observed in living mice, under fasting conditions and in the presence of normal glucose levels.…”
Section: Discussionsupporting
confidence: 89%
“…The apparent metabolic activation of this nervous district faced an opposite pattern in the brain cortex that showed a generalized reduction in tracer uptake [8]. By contrast, it extended to the psoas muscles of the same patients, suggesting a link between the metabolic pattern of the second motoneuron and its effector [9].…”
Section: Introductionmentioning
confidence: 92%
“…The present study confirms that the metabolic activation of skeletal muscle, observed in ALS patients, also occurs in the SOD1 G93A experimental model [9]. The increase in FDG accumulation rate was observed in living mice, under fasting conditions and in the presence of normal glucose levels.…”
Section: Discussionsupporting
confidence: 89%
“…The present study con rms that the increased skeletal muscle FDG uptake observed in ALS patients also occurs in the SOD1 G93A experimental model [9]. The increase in FDG accumulation rate was observed in living mice, under fasting conditions and in the presence of normal glucose levels.…”
Section: Discussionsupporting
confidence: 84%
“…The apparent metabolic activation of this nervous district faced an opposite pattern in the brain cortex that showed a generalized reduction in tracer uptake [8]. By contrast, it extended to the psoas muscles of the same patients, suggesting a link between the metabolic pattern of the second motoneuron and its effector [9]. FDG uptake is commonly considered an index of glucose consumption.…”
Section: Introductionmentioning
confidence: 99%